Study on the chemical properties of juvenile Acacia Mangium - Awang, Ahmad Azwan (2010)
In line to develop substitute material in wood base industry, research had been carried out for new material. The objective of this study is to investigate the chemical properties of juvenile Acacia mangium and to evaluate its potential as a material to develop a wood product. Samples were taken from UiTM Jengka Forest Reserve. Seven chemical properties of juvenile Acacia mangium was determine, namely cold water solubility, hot water solubility, 1% NaOH solubility, percentage of lignin, holocellulose, cellulose and extractive. In this study, it shown that the cold water solubility was 11%, hot water solubility 12.5% and 1% NaOH 18.5%. The percentage of lignin was 25%, cellulose 13%, holocellulose 16.6% and extractive 20.7% respectively.